Mental Health: A Hard Sell - Pettigrew, Simone; Pescud, M.; Donovan, Robert (-, 2010)
This study addresses the need to ‘sell’ the idea of mental health in an environment where there is a focus on mental illness instead of mental health, and where mental illness is highly stigmatised. Focus groups and individual interviews were conducted with 111 Western Australians aged 40 years and older to explore their perceptions of mental health and mental illness to inform social marketing efforts to increase mental health literacy. The findings indicate that a mental health promotion campaign directed at mature adults should recognise the prevention focus that is likely to be dominant among members of this group and hence emphasise the response efficacy of the recommended behaviours.